Chagas Disease Drug Discovery in Latin America—A Mini Review of Antiparasitic Agents Explored Between 2010 and 2021 - de Oliveira, Ramon G.; Cruz, Luiza R.; Mollo, María C.; Dias, Luiz C.; Kratz, Jadel M. (Frontiers in Chemistry, 2021)
Chagas disease is a neglected tropical disease caused by the protozoan parasite Trypanosoma cruzi that endangers almost 70 million people worldwide. The only two drugs that are currently approved for its treatment, benznidazole and nifurtimox, have controversial efficacy in adults and restricting safety issues, leaving thousands of patients without a suitable treatment. The neglect of Chagas disease is further illustrated by the lack of a robust and diverse drug discovery and development portfolio of new chemical entities, and it is of paramount importance to build a strong research and development network for antichagasic drugs. Focusing on drug discovery programs led by scientists based in Latin America, the main endemic region for this disease, we discuss herein what has been published in the last decade in terms of identification of new antiparasitic drugs to treat Chagas disease, shining a spotlight on the origin, chemical diversity, level of characterization of hits, and strategies used for optimization of lead compounds. Finally, we identify strengths and weaknesses in these drug discovery campaigns and highlight the importance of multidisciplinary collaboration and knowledge sharing.